Bioethanol Potential of Energy Sorghum Grown on Marginal and Arable Lands - Tang, Chaochen; Li, Songbo; Li, Meng; Xie, Guang H. (Frontiers in Plant Science, 2018)
Field experiments were conducted in marginal lands, i.e. sub-humid climate and saline-land (SHS) and semi-arid climate and wasteland (SAW), to evaluate ethanol potential based on the biomass yield and chemical composition of biomass type (var. GN-2, GN-4, and GN-10) and sweet type (var. GT-3 and GT-7) hybrids of energy sorghum [Sorghum bicolor (L.) Moench] in comparison with sub-humid climate and cropland (SHC) in northern China. Results showed that environment significantly (p<0.05) influenced plant growth, biomass yield and components, and subsequently the ethanol potential of energy sorghum. Biomass and theoretical ethanol yield of the crop grown at SHS (12.2 t ha-1 and 3,425 L ha-1, respectively) and SAW (8.6 t ha-1 and 2,091 L ha-1, respectively) were both statistically (p<0.001) lower than values at the SHC site (32.6 t ha-1 and 11,853 L ha-1, respectively). Higher desirable contents of soluble sugar, cellulose, and hemicellulose were observed at SHS and SHC sites, while sorghum grown at SAW possessed higher lignin and ash contents. Biomass type sorghum was superior to sweet type as non-food ethanol feedstock. In particular, biomass type hybrid GN-10 achieved the highest biomass (17.4 t ha-1) and theoretical ethanol yields (5,423 L ha-1) after averaging data for all environmental sites. The most productive hybrid, biomass type GN-4, exhibited biomass and theoretical ethanol yields greater than 42.1 t ha-1 and 14,913 L ha-1, respectively, at the cropland SHC site. In conclusion, energy sorghum grown on marginal lands showed a very lower ethanol potential, indicating a considerable lower possibility for being used as commercial feedstock supply when compared with that grown on regular croplands. Moreover, screening suitable varieties may improve energy sorghum growth and chemical properties for ethanol production on marginal lands.